1979
DOI: 10.1007/bf01887499
|View full text |Cite
|
Sign up to set email alerts
|

The continent ileostomy (Kock pouch): Roentgenologic features

Abstract: The principles of construction of a continent ileostomy by means of a reservoir as originally described by Kock are reviewed. Roentgenologic studies in 5 patients with such reservoirs are described. There may be a correlation of incontinence with peristaltic activity as well as nipple valve extrusion. The radiologic features are explained in terms of the anatomy of the reservoirs. One patient with postoperative ileitis is described. Roentgenologic studies may be of particular value to the surgeon in follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Double-contrast radiology is a valuable procedure in the workup of patients with malfunctioning continent ileostomies [2][3][4][5][6]. In the present study, a defective con- Of 32 patients in w h o m some degree of detachment of the reservoir from the abdominal wall was found during surgery, this defect was either suspected or diagnosed radiologically in 20.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Double-contrast radiology is a valuable procedure in the workup of patients with malfunctioning continent ileostomies [2][3][4][5][6]. In the present study, a defective con- Of 32 patients in w h o m some degree of detachment of the reservoir from the abdominal wall was found during surgery, this defect was either suspected or diagnosed radiologically in 20.…”
Section: Discussionmentioning
confidence: 57%
“…Other authors [2][3][4][5][6] have shown that radiologic studies improve the assessment of complications of the continent ileostomy, but perusal of the literature reveals no systematic radiologic study of dysfunctioning reservoirs.…”
mentioning
confidence: 99%
“…These advanced operations require follow-up investigations in order to identify and treat postoperative complications. Radiologic evaluation proved to be of great value in the development of Kook's continent ileostomy (2,3,10).…”
mentioning
confidence: 99%
“…Ileorectal anastomosis was not always a satisfactory alternative (1). In the late sixties, KOCK (5, 6) introduced a new surgical procedure for a continent ileostomy (2,3,5,6,10). This was a technically difficult operation, often with postoperative complications, while the patient still suffered the drawback of an ileostomy (17).…”
mentioning
confidence: 99%